WARRANTIES AND CERTAINTY OF LEGAL PROTECTION OF CHILDREN FROM CIGARETTE ADDICTION ON 113 SMOKE FREE AREA POLICIES IN INDONESIA - HERY CHARIANSYAH, SH , M. ABDOEL MALIK R., SH.I. (MTCC, John Hopkins n The Union, 2015)
Background: tobacco smoking prevalence among children in indonesia has reached at alrming level. Almost all of existing data showed major increament of smoking prevalence among children in all age groups. Children are also vulnerable to passive smoking in which they are exposed to cigarette smoke both at public places and home. Actually, indonesian constitution are guaranteed safekeeping the children from any threats to life, growth, and development. Therefore, the government is responsible for protecting children from tobacco addiction and exposure to second hand smoke. This paper is going to delineate legal guarantee and certanity of child protection aspect whithin smoke free area (sfa) policies in provincial and city level. Methods: this study is normative legal (juridical normative) research. A total of 113 smoke free area policies from all over indonesia were analyzed by legislation and conceptual approach. Results: data revealed that 57 of sfa policies had strong legal guarantee because of in local regulation format, and also accordance with the law no. 36 year 2009 on health. 112 policies which shaped as local regulation, governor/mayor regulation, and governor/mayor decree were recognized in the legal system. Another one policies in governor/mayor circulation format that might not provide legal gurantee for child protection. In general, the local sfa plocies were widely differrent between region that could be reflected from variation of smoke free area definition, scope, sanction, and person in charge for implementation. Among 113 sfa policies, 99.11% include health facilities in sfa coverage, 98.23% for education facilities, and 95.5% of childcare facilities. Moreover, 98% of policies clearly regulated person in charge for implementation, 62.83% provided both criminal and administrative sanction. Conclusion: in summarry, most of smoke free area policies in local level were able to provide legal guarantee for child protection. Presistent all support from all stake holder are urgently needed so those policies are not only strong in paper but also well implemented. Keywords: local regulation, child's rights, rule of law, cigarette addiction